Parents’ Participation in School Health Examinations for Their Adolescent Children in Finland - Kivimäki, Hanne M. (SAGE Publications Inc., 2022)
Engaging parents in school health examinations can promote adolescents' well-being. We examined parents' participation in universal school health examinations in Finland reported by adolescents in school surveys (14 to 16-year-olds, N = 58,232). Further we studied variation between service providers and schools, and student and school-level factors in participation. National data were analyzed using multilevel logistic regression models. Less than half of the adolescents reported parents' participation. The variation between service providers and schools was large. Non-participation was associated with mother's low education, students' immigrant background, daily health complaints, heavy drinking, and discussion difficulties with parents. Boys and those who did not live with both mother and father had a higher risk for parents' non-participation. Adolescents with a long-term illness or being bullied reported participation more often. Inviting parents and the school health nurse resource were not associated with participation. Our results raise the question of barriers to participation in health examinations.